A Christology with a Historical and Experiential Perspective - Polo Medina, Paola (2020)
This paper aims to bring us closer to a simple and understandable reading of the need to approach the Christological theme, faith in the divinity of Jesus, from the historical perspective and the human experience. The starting point is the conviction that Christology can be better understood if the divinity of Jesus is read from history and not from history. If it is affected by the human experience of those who knew him and discovered his divinity in life itself. Likewise, in this way we move away from the twisted positions that today continue to affirm that historical experience is not necessary, thus leaving us a very distant and abstract Jesus Christ, who is little understandable and as little credible for our times.